IMPACT ON THE APPLICATION OF INSULATION IN BUILDINGS TO ACHIEVE THERMAL COMFORT (A CASE STUDY: LAUSER OFFICE BUILDING IN BANDA ACEH) - Lisa, Nova Purnama; Zuraihan, Zuraihan (Department of Architecture, Faculty of Science and Technology, UIN Maliki Malang, 2014)
From the results of research studies on the impact of the use of insulation in buildings, reducing solar radiation on buildings to improve indoor comfort by applying the Principles of radiation reduction in buildings naturally using insulation application that serves as an insulator against the building materials, use of thermal insulation in particular mounted on the roof of the building and the walls are located on second floor and the third floor Lauser office building, Calculate the cooling load for each room that was on second floor and the third floor based on the geographical location or position of the building, climate data, building material data , and the intensity of the spatial characteristics which include lighting, solar radiation, user activity and electrical appliances being used. The calculation is done with the help of Ecotech v.5, 2011. The location and position on the third floor of a building with a flat roof cast concrete, so that the heat absorbed by the platform, and two times greater than the amount of heat radiation is absorbed by the material in the direction of the light falling the sun is at an angle 30Â°C. The simulation results on the building with the addition of thermal insulation on all walls and the roof of the inside of the foam material ultrafolmadehid, without changing the model building and similar activities in accordance with the existing condition and the condition of the room using the air conditioner at a temperature of 18-26Â°C, indicating a decrease in cooling load signifinikan in any space reaches 40% of the total cooling load required on the lauser office building. Comparing the simulation results Ecotech temperature v.5 2011 with field measurements as a validation of the simulation results in order to achieve thermal comfort in buildings and can menggurangi use energy consumption in buildings and can be used as a reference in planning space-based conditioning systems energy efficient.